2020
DOI: 10.18632/aging.102735
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 34 genes conferring genetic and pharmacological risk for the comorbidity of schizophrenia and smoking behaviors

Abstract: The prevalence of smoking is significantly higher in persons with schizophrenia (SCZ) than in the general population. However, the biological mechanisms of the comorbidity of smoking and SCZ are largely unknown. This study aimed to reveal shared biological pathways for the two diseases by analyzing data from two genome-wide association studies with a total sample size of 153,898. With pathway-based analysis, we first discovered 18 significantly enriched pathways shared by SCZ and smoking, which were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Changes in the methylation on CpGs in the promoter region of AXL and PTPRO genes. Disease risk in later life Breton et al 2009 52 Cigarette smoke Hypomethylation on the glutamate-cysteine ligase catalytic subunit (GCLC) gene COPD Cheng et al 2016 53 Cigarette smoke CpG methylation Of gene AIRE, PENK and SLC6A3 Non-small cell lung cancer Ma et al 2019 54 Cigarette smoke DNA methylation in white blood cells Cardiovascular diseases Chatziioannou et al 2017 55 Cigarette smoke DNA methylation Schizophrenia Ma et al 2020 56 Indoor air pollution caused by smoky coals with high benzo(a)pyrene (BaP) and quartz levels CDKN2A, DLEC1, CDH1, DAPK, RUNX3, APC, and WIF1 DNA methylation in the promoter region Primary non-small cell lung cancer (NSCLC) Huang et al 2018a 57 Biomass smoke miR-126 and miR-155 Cardiovascular diseases Ruiz-Vera et al 2019 58 Second-hand smoke Altered methylation of major repetitive DNA elements including LINE L1, IAP LTR and SINE B1 Lung cancer Tommasi et al 2012 59 Second-hand smoke DNA methylation of several CpG loci Bladder carcinoma Wilhelm-Benartzi et al 2011 60 Second-hand smoke CpG methylation within FOXP3 and IFNγ loci Asthma Runyon et al 2012 61 Smoke and second-hand smoke Altered methylation of GSTP1, FHIT, and CDKN2A, SCGB3A1 and BRCA1genes Breast cancer Callahan et al 2019 …”
Section: Air Pollution and Epigenetic Modificationsmentioning
confidence: 99%
“…Changes in the methylation on CpGs in the promoter region of AXL and PTPRO genes. Disease risk in later life Breton et al 2009 52 Cigarette smoke Hypomethylation on the glutamate-cysteine ligase catalytic subunit (GCLC) gene COPD Cheng et al 2016 53 Cigarette smoke CpG methylation Of gene AIRE, PENK and SLC6A3 Non-small cell lung cancer Ma et al 2019 54 Cigarette smoke DNA methylation in white blood cells Cardiovascular diseases Chatziioannou et al 2017 55 Cigarette smoke DNA methylation Schizophrenia Ma et al 2020 56 Indoor air pollution caused by smoky coals with high benzo(a)pyrene (BaP) and quartz levels CDKN2A, DLEC1, CDH1, DAPK, RUNX3, APC, and WIF1 DNA methylation in the promoter region Primary non-small cell lung cancer (NSCLC) Huang et al 2018a 57 Biomass smoke miR-126 and miR-155 Cardiovascular diseases Ruiz-Vera et al 2019 58 Second-hand smoke Altered methylation of major repetitive DNA elements including LINE L1, IAP LTR and SINE B1 Lung cancer Tommasi et al 2012 59 Second-hand smoke DNA methylation of several CpG loci Bladder carcinoma Wilhelm-Benartzi et al 2011 60 Second-hand smoke CpG methylation within FOXP3 and IFNγ loci Asthma Runyon et al 2012 61 Smoke and second-hand smoke Altered methylation of GSTP1, FHIT, and CDKN2A, SCGB3A1 and BRCA1genes Breast cancer Callahan et al 2019 …”
Section: Air Pollution and Epigenetic Modificationsmentioning
confidence: 99%
“…By conducting a PPI network enrichment analysis, we observed that these risk genes were significantly interacted with each other in a subnetwork (PPI enrichment P = 0.0016, Supplemental Figure S6c), suggesting that these identified genes may have collectively biological functions on PBC risk 34,37 . Furthermore, we also performed a GO-term enrichment analysis according to three different categories (i.e., CC, MF, and BP), and found that several GO-terms were notably overrepresented (Supplemental Figures S6d, and S7-S9), such as interferon-gamma-mediated signaling pathway (P = 2.8×10 −4 ) and neutrophil activation involved in immune response (P =7.3×10 −4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hypergeometric test was used to evaluate the significant enrichment for the disease- and GO-term enrichment analysis. The Jaccard distance algorithm 34 was used to assess the similarities among pathways.…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies have demonstrated that disease-associated genes with similar functions may collectively contribute risk to complex diseases [ 69 73 ], including asthma [ 74 ]. Consistently, our GeneMANIA-based PPI network analysis demonstrated that these 31 genes were highly interacted with each other based on multiple layers of evidence.…”
Section: Discussionmentioning
confidence: 99%